Euro-seminar 2002, Berlin-Brandenburg, Germany - (:unkn) unknown (My University, 2026)
Euro-seminar 2002, Berlin-Brandenburg, Germany Round Table Discussion and Exhibition Participation in Workshops, Symposia and Exchanges